Identification and characterization of in vitro expanded hematopoietic stem cells. (16th August 2022) - Che, James L C; Bode, Daniel; Kucinski, Iwo; Cull, Alyssa H; Bain, Fiona; Becker, Hans J; Jassinskaja, Maria; Barile, Melania; Boyd, Grace; Belmonte, Miriam; Zeng, Andy G X; Igarashi, Kyomi J; et al.
Abstract: Hematopoietic stem cells (HSCs) cultured outside the body are the fundamental component of a wide range of cellular and gene therapies. Recent efforts have achieved > 200‐fold expansion of functional HSCs, but their molecular characterization has not been possible since the majority of cells are non‐HSCs and single cell‐initiated cultures have substantial clone‐to‐clone variability. Using the Fgd5 reporter mouse in combination with the EPCR surface marker, we report exclusive identification of HSCs from non‐HSCs in expansion cultures. By directly linking single‐clone functional transplantation data with single‐clone gene expression profiling, we show that the molecular profile of expanded HSCs is similar to proliferating fetal HSCs and reveals a gene expression signature, including Esam, Prdm16, Fstl1, and Palld, that can identify functional HSCs from multiple cellular states. This "repopulation signature" (RepopSig) also enriches for HSCs in human datasets. Together, these findings demonstrate the power of integrating functional and molecular datasets to better derive meaningful gene signatures and opens the opportunity for a wide range of functional screening and molecular experiments previously not possible due to limited HSC numbers. Synopsis: This study presents a method for prospectively isolating HSCs from in vitro cultures. Paired molecular and functional analyses on a large number of individual clones identifies a gene expression signature that can identify functional HSCs from multiple cellular states. EPCR, ESAM and Fgd5 permit prospective identification of functional HSCs from in vitro clones. Molecular profiling of purified expanded HSCs shows that their profile is similar to proliferating fetal HSCs. A specific gene signature identifies repopulating HSCs from a wide range of different cellular states, including human HSCs. Abstract : This study presents a method for prospectively isolating HSCs from in vitro cultures. Paired molecular and functional analyses on a large number of individual clones identifies a gene expression signature that can identify functional HSCs from multiple cellular states.